O saneamento ambiental como condição primacial à sadia qualidade de vida e fator estruturante do Estado Democrático de Direito Brasileiro - Fuller, Greice Patricia (2011)
This thesis analyses environmental sanitation that, in addition to being of undeniable importance, is an issue that hinders the right to the fulfillment of human dignity. It is one of the most serious and absurd public health problems of our country and the crisis in this area is indifferent to the pain of those who are not granted this fundamental right. The theme is initially analyzed focusing on the social mission of cities since they are determinant in the search for the well-being of citizens and environmental balance. Following this thought, the principals of sustainability and human dignity are inseparable themes for the development of the study. The thesis follows with a conceptual and normative study regarding environmental sanitation emphasizing it as a fundamental human right for quality of life, subsuming it in the Federal Constitution, as well as in the sub-constitutional underlying framework. Furthermore, the well established link between sanitation and health is developed observing the regional and national contrasts in terms of the rendering of services in this area proving that environmental degradation, as a result of the absence or deficiency of an efficient sanitation system, generates a negative impact on absolutely all aspects of the environment, whether these are cultural, natural, work related or artificial, evaluated in their specificities. From then on, we conclude that environmental sanitation is fundamental for the structuring and implementation of Brazil s democratic rule-of-law state, affecting it in its principals, fundaments and objectives that will provide the legal confrontation of issues that are inherent to the preventive and repressive mechanisms aimed at changing the present scenario regarding the subject